A MANIFESTAÇÃO DO MEDO NA NARRATIVA FANTÁSTICA: a construção literária e cinematográfica em It - A Coisa, de Stephen King e Andy Muschietti - COSTA, José Antonio Moraes (2021)
The aim of this study is to analyze how the construction of fear occurs in the novel It - A novel, by the American writer Stephen King and in the audiovisual work of the same name by filmmaker Andy Muschietti, from the perspective of fantastic literature. To do so, built on the literary scholarship of TzvetanTodorov (1981), Remo Cesarani (2006) David Roas (2014), Noel Carroll (1999), Yu-Fu Tuan (2005), Zygmunt Bauman (2008) and Júlio França (2017). On audiovisual studies, the works of Michel Chion (2008), Jacques Aumont (2012), Adriano Messias (2016) and Jennifer Sjill (2017). As for the methodology, a research is bibliographic, exploratory and qualitative. A content analysis model is adopted. The investigation of these works allows studies on horror, as they represent the manifestation of various fears of man. The fantastic genre was consolidated by inserting the real and unreal in his texts. As ambiguities in the texts establish astonishment, a restlessness, a fear, a mystery and a fear. An end of exhibition in the reader / viewer or effect of fear, such as fantastic literary or cinematic narratives, usually exhibits supernatural events, which abruptly, insertion or isolation in the natural world. The capacity of this genre to enter worlds that escape human rationality, stimulate or cinema to produce a series of terrifying audiovisual productions. In this sense, as the works analyzed in this dissertation present a hesitation, or astonishment, a doubt and an uncertainty, as indicated in Todorovian studies. In addition, as results, see how King's literary work and the film Muschietti are interpreting horror in different ways, however, both preserved as characteristics of the fantastic. In the novel, fear can be caused by a series of figures such as the occurrence of supernatural images, haunted spaces, human monstrosities and physical disorders. In the audiovisual product, the visual, sound and assembly mechanisms are basic for the construction of fears, unusual and fantastic ambiguity.